Um olhar de gênero sobre a reconstrução da agricultura em Abaetetuba, Pará. - MOURÃO, Patrícia de Lucena (Universidade Federal do Pará, 2021)
The revelation of the negative aspects of modernization in agriculture upon women, men and the environment, brought up the need to develop alternative ways of food production establishing new relations with local eco-systems. In this view, the Agroecology has an important contribution because it relates the technological model to the productive aspects, environmental, social and economic, including gender relationships. This study analyses production and reproduction strategies of familial agriculture, identifying potentialities and limits for the development of sustainable agro systems and to the fair gender relationship. This strategies research was made among land workers (men and women), from the region of Abaetetuba – Pará, participants of the Center – “Tecnologias Alternativas Tipiti”. With the result of this research, we found out that the familial agricultural strategies turn to the construction of the agroecologic sustainability instead of the gender equality. This is because of the poor understanding that the transformation of the technological standard has to be related to men and women performance and social position, and that themselves are able to change. We hope to help this process with this study.